Synergistic Activation of Inflammatory Cytokine Genes by Interferon-γ-induced Chromatin Remodeling and Toll-like Receptor Signaling - Qiao, Yu (2013)
Synergistic activation of inflammatory cytokine genes by interferon-γ (IFN-γ) and Toll-like receptor (TLR) signaling is important for innate immunity and inflammatory disease pathogenesis. Enhancement of TLR signaling, a previously proposed mechanism, is insufficient to explain strong synergistic activation of cytokine production in human macrophages. Rather, we found that IFN-γ induced sustained occupancy of transcription factors STAT1, IRF-1 and associated histone acetylation at promoters and enhancers at the TNF, IL6 and IL12B loci. This priming of chromatin did not activate transcription, but greatly increased and prolonged recruitment of TLR4-induced transcription factors and RNA polymerase II to gene promoters and enhancers. Priming sensitized cytokine transcription to suppression by Jak inhibitors. Genome-wide analysis revealed pervasive priming of regulatory elements by IFN-γ, and linked coordinate priming of promoters and enhancers with synergistic induction of transcription. Our results provide a synergy mechanism whereby IFN-γ creates a primed chromatin environment to augment TLR-induced gene transcription.